A new approach on the evaluation of magnesium wastes in the magnesium borate synthesis using the novel method of ultrasonic irradiation - Kipcak, Azmi Seyhun; Derun, Emek Moroydor (SPRINGER, 2016)
The present study aims to evaluate waste magnesium in magnesium borate synthesis using a novel method of ultrasonic irradiation. For this purpose, waste magnesium is used as a raw material both with boric acid (H3BO3) and boron oxide (B2O3). Syntheses are conducted by directly immersing an ultrasonic probe in a glass reactor, and the reaction parameters are set between 60-80 degrees C and 5-20 min. Characteristic analyses of the synthesized products are conducted by the techniques of X-ray diffraction, Fourier transform infrared spectroscopy, Raman spectroscopy, and scanning electron microscope (SEM). Products B2O3 contents and reaction yields are also investigated. Results showed that admontite [MgO(B2O3)(3)center dot 7(H2O)] and mcallisterite [Mg-2(B6O7(OH)(6))(2)center dot 9(H2O)] types of magnesium borates minerals are synthesized. SEM analysis showed that the products particle sizes are approximately between 750 nm and 3.58 mu m for mcallisterite, 474 nm and 5.10 mu m for admontite. The reaction yields are found between 22 and 51 %. [GRAPHICS] .
Keywords: Magnesium borate; Magnesium wastes; Ultrasonic irradiation; THERMAL-CONVERSION; MASS-PRODUCTION; SONOCHEMISTRY; FABRICATION; Chemistry